Prevalence and factors associated with obesity among adult at the Kampong Kolam, East Coast Malaysian peninsula- A cross sectional study - San San, Oo; U.S. Mahadeva, Rao; Thant, Zin (2017)
Objective: This study assesses the prevalence of obesity and its associated factors among adults aged 18 y and above at the Kampaung kolam, Kuala Terengganu, Malaysia. Methods: This cross-sectional survey comprised of a semi-structured face to face interview questionnaire and collected anthropometric measurements and sex specific waist circumference in cm. The study population was 70 in total with 21 (30%) males and 49 (70%) females aged 18 y and above were selected by universal sampling. Body mass index (BMI) was used for weight status and sex specific waist circumference (WC) in cm was used for assessment of abdominal or central obesity at risk of metabolic complications associated with obesity. Results: Among men, the prevalence of underweight was 9.5%, normal weight 57.1%, overweight 14.3% and obesity 19.1%, while among women, the prevalence of underweight was 12.2%, normal weight 53.1%, overweight 14.3% and obesity 20.4%. Overall, 18 (25.7%) was obese and 52 (74.3%) was non-obese while sex specific WC in cm 19 (27.1%) was abdominal obese who were at risk of metabolic complication associated with obesity and 51 (72.9%) was not at risk. In chi-square association tests revealed that among respondents, currently married, unemployed and having family history with obesity were associated with generalized obesity while respondents who were currently married and having fast food frequently were associated with abdominal obesity and respondents who being currently married, unemployed and having fast food frequently were more likely to obese in generalized as well as abdominally. Conclusion: There was no association between generalized, abdominal and generalized and abdominal obesity with age, gender, education, flat floor structure, dietary patterns and habits, physical activities, sleep pattern and knowledge and attitude level towards obesity but those factors can be utilized in effective health promotion programmers of weight management strategies by targeting those factors in design for prevention of hypertension, diabetes and related cardio vascular diseases CVD.